Produksi dan Komposisi Susu Kambing Peranakan Ettawa yang Diberi Suplemen Daun Katu (Sauropus androgynus (L.) Merr) pada Awal Masa Laktasi (Milk Production and Milk Composition of Ettawa Crossbred Goat, Fed Katu Leaves (Sauropus androgynus (L.) Merr) as - Marini Putri Marwah; Yustina Yuni Suranindyah; Tridjoko Wisnu Murti (Faculty of Animal Science, Universitas Gadjah Mada, 2010)
This experiment was aimed to evaluate the effect of katu leaves as feed supplement on milk production and milk composition of Ettawa Crossbred goat during early lactation. The experiment was conducted in the village of Kemirikebo, Girikerto, Turi, Sleman started from June, 27 until August, 27 2009. The experiment used 8 pregnant goats weighing 36 to 55 kg. The goats were divided into 2 treatments, those were control and treatment groups. The goats incontrol group received basal feed as much as 10% dry matter of body weight, consisted of calliandra and concentrates with a ratio of 9 to 1 respectively. The treated goats were fed with the same basal feed as those in the control group andsupplemented with katu leaves at 0,06% of bodyweight. The examination was conducted to collect data on feed intake, milk production, composition of colostrum and milk. Data were statistically analyzed with T-test. The result showed that katu leaves supplementation as much as 0,06% of body weight was able to increase protein level of colostrum significantly but had no significant effect on feed intake, milk production, and milk composition.(Key words: Ettawa Crossbred goat, Katu leaves, Milk production and composition)